Determinants Of Capital Flight In Malaysia - Puah, Chin Hong; Liew, Siew-Ling; Mohammad Affendy, Arip (JIFE-Journal.Org, 2012)
This study was intended to investigate factors affecting capital flight in Malaysia. The study used time series data from first quarter 1991 through fourth quarter 2008 and the data were tested using the Augmented Dickey-Fuller unit root test, Johansen-Juselius cointegration test, and vector error-correction modeling. Empirical findings indicated a stable long-run relationship between the variables under study. Foreign direct investment and the stock market were found to have a positive impact on capital flight, whereas real gross domestic product (GDP), budget deficit, and interest rate were negatively related to capital flight. In addition, real GDP, interest rate, and budget deficit can Granger cause capital flight in the short-run.